Projection of HIV prevalence among individuals aged 15-49 years in Cambodia using Holt’s double exponential smoothing technique - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Cambodia from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.6 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among people aged 15-49 years will continue to decline significantly over the out of sample period. Therefore, we encourage authorities to strengthen preventive measures among key populations who are experiencing an increase in HIV seroprevalence
Keywords: Exponential smoothing; Forecasting; HIV prevalence